Angka Kejadian serta Faktor-Faktor yang Mempengaruhi Gangguan tidur (Insomnia) Pada Lansia di Panti Sosial Tresna Werda Wana Seraya 1 Denpasar Bali Tahun 2013 - Putu Arysta Dewi; I Gusti Ayu Indah Ardani (Universitas Udayana, 2014)
Background: the incidence Rate of insomnia will increase as you get older. In the other words, the symptoms of insomnia often occurs in the elderly even almosthalf of the number of elderly reported having difficulty starting and maintainingsleep.Objective: to know the numbers of elderly who experience sleep disorders(insomnia) and the factors that affect sleep disorders (Insomnia) in Panti TresnaWerda Wana Seraya Denpasar.Materials and methods: a method of this research using design descriptive ofcross-sectional non-experimental, which use of samples 15 peoples after ininclusion and exclusion. Through live interview by using a questionnaire at PantiTresna Werda Wana Seraya Denpasar.Result : There are 6 elderly (40%) who suffering insomnia with several factorsaffecting based on age, there are 4 elderly 60 – 70 years (66,6%), there are 2elderly 71 – 80 years (22,2%). Based on sex, there are 1 elderly man (25%) and 5elderly women (45,5%). Based on bad habit of sleeping, there are 1 elderly(16,6%) that has bad habit or bad sleeping patterns. Based on the underlyingdisease, there are 4 elderly (66,6%). Based on mental disorder such as majordepression or anxiety , there are 3 elderly or only 50% who having depression oranxiety.